PEMBUATAN MESIN PENGADUK ADONAN UNTUK MENINGKATKAN PRODUKSI PADA USAHA KECIL PENJUAL MARTABAK - Widodo, Rahmat Doni; Khumaedi, Muhammad (Universitas Negeri Semarang, 2017)
This Â devotion Â activity Â carried Â out Â with Â the Â aim Â to Â help Â problems Â that Â were Â be- ingÂ facedÂ byÂ smallÂ businessÂ sellerofÂ martabakÂ â€œBangkaâ€. ActivityÂ specific targetÂ ofÂ thisÂ de- votionÂ isÂ toÂ generateÂ theÂ externalÂ aspectsÂ ofÂ productionÂ suchÂ as:Â makingÂ doughÂ mixer machine of sweet martabak that is rotated with electric motor. The methods used for the imple- mentation of this activity was done in various ways that support each other, namely: coordina- tion, machine building, training of machine operating, accompanying partners during the ac- tivities in progress and evaluating activity results. The result of this devotion activity is dough stirring machine with Â¼ PK that time of the stirring becomes five times faster, stirring dough results Â become Â smoother, Â production Â increases, Â as Â well Â as Â income Â and Â increasing Â its Â profits